El Chino - Say, Allen (Boston : Houghton Mifflin Co., 1990)
A biography of Bill Wong, a Chinese American who became a famous bullfighter in Spain.
Keywords: El Chino -- Juvenile literature; El Chino; Bullfighters -- United States -- Biography -- Juvenile literature; Bullfighters